2023
DOI: 10.3390/pharmaceutics15020321
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microsphere Structures in Bottom-Up Bone Tissue Engineering

Abstract: Bone defects have caused immense healthcare concerns and economic burdens throughout the world. Traditional autologous allogeneic bone grafts have many drawbacks, so the emergence of bone tissue engineering brings new hope. Bone tissue engineering is an interdisciplinary biomedical engineering method that involves scaffold materials, seed cells, and “growth factors”. However, the traditional construction approach is not flexible and is unable to adapt to the specific shape of the defect, causing the cells insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 235 publications
(194 reference statements)
0
1
0
Order By: Relevance
“…[6][7][8] Recently, biochanin A (BCA), a methylated derivative of isoflavone genistein, has attracted great attention because of its promising therapeutic potential, including antioxidant, antifibrotic, anti-inflammatory, anti-infective, and anticarcinogenic effects. [9][10][11][12] As a chemotherapeutic agent, the previous studies have reported in vitro anticancer efficacy of BCA on various cancer cell lines, including prostate, breast, lung, and pancreatic cancer cells, by the induction of apoptosis and inactivation of AKT/ERK signaling. [13,14] However, the clinical efficacy of BCA is limited by its low oral bioavailability and high body clearance, owing to poor aqueous solubility.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Recently, biochanin A (BCA), a methylated derivative of isoflavone genistein, has attracted great attention because of its promising therapeutic potential, including antioxidant, antifibrotic, anti-inflammatory, anti-infective, and anticarcinogenic effects. [9][10][11][12] As a chemotherapeutic agent, the previous studies have reported in vitro anticancer efficacy of BCA on various cancer cell lines, including prostate, breast, lung, and pancreatic cancer cells, by the induction of apoptosis and inactivation of AKT/ERK signaling. [13,14] However, the clinical efficacy of BCA is limited by its low oral bioavailability and high body clearance, owing to poor aqueous solubility.…”
Section: Introductionmentioning
confidence: 99%